PANDANGAN MAQAá¹¢ID AL-SHARIâ€™AH DALAM FATWA ULAMA KONTEMPORER TENTANG NIKAH MISYAR - M. Halilurrahman; Imam Edi Supeno (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The mis'yar marriage event that arises public gmudity including in Indonesia has caused debate among contemporary scholars. From the fatwa that has been issued by contemporary scholars about marriage mis'yar, the most highlighted issue is about the purpose of shari'ah (maqaá¹£id al-shari'ah) in marriage mis'yar becomes the main reason that is debated among contemporary scholars. Researchers want to discuss the problem that is 1) How the basis for the establishment of contemporary scholars about marriage mis'yar. 2) How the fatwa of the scholars' contemporary on marriage mis'yar is viewed from the point of maqaá¹£id al-shari'ah. This research uses a qualitative approach with a type of research that is library. Legal material analysis techniques include content analysis, and critical analysis of the fatwa is reviewed from maqaá¹£id al-shari'ah. The results of the study (1) there are two groups of scholars' contemporary, namely ulama' allowing marriage mis'yar Yusuf al-Qardhawi and Wahbah ZuhailÄ« and ulama' prohibit marriage mis'yar 'Abd al-'Aziz bin al-Baz and 'Umar Sulaimá¾±n al-Aá¹£qar. (2) The fatwa of contemporary scholars' that permits and prohibits marriage of mis'yar is viewed from the perspective of maqaá¹£id al-shari'ah, on the basis of the consideration that its efficacy is far greater than its benefits.